Quantum Dot Devices - Wang, Zhiming M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Quantum dots as nanomaterials have been extensively investigated in the past several decades from growth to characterization to applications. As the basis of future developments in the field, this book collects a series of state-of-the-art chapters on the current status of quantum dot devices and how these devices take advantage of quantum features. Written by 56 leading experts from 14 countries, the chapters cover numerous quantum dot applications, including lasers, LEDs, detectors, amplifiers, switches, transistors, and solar cells. Quantum Dot Devices is appropriate for researchers of all levels of experience with an interest in epitaxial and/or colloidal quantum dots. It  provides the beginner with the necessary overview of this exciting field and those more experienced with a comprehensive reference source.   Covers the current status and future trends in  research on quantum dot devices Features contributions from leading experts in each pplications area Suitable for experienced researchers as well as those new to the field.
Preface -- 1. Optically injected single-mode quantum dot lasers.- 2. Exotic Behavior in Quantum Dot Mode-locked Lasers: Dark Pulses and Bistability -- 3. Spectral Splitting Effects and Their Influence to the Performance of Quantum Dot Mode Locked Lasers -- 4. Mode-locked semiconductor lasers with optical injection -- 5. Catastrophic Optical Damage in Quantum Dot Lasers -- 6. Post-Growth Intermixing of GaAs Based Quantum Dot Devices -- 7. Photonic Crystal Cavity Lasers -- 8. InGaAs Submonolayer Quantum-Dot Photonic-Crystal LEDs for Fiber-Optic Communications -- 9. Quantum Optical Transistor and Other Devices Based on Nanostructures -- 10. Quantum Dot Switches: Towards Nanoscale Power-Efficient All-Optical Signal Processing -- 11. Ultrafast Terahertz Dynamics and Switching in Quantum Dots -- 12. Nonlinear optics and saturation behavior of quantum dot samples under continuous wave driving -- 13. Quantum Dots with Built-in Charge for Enhancing Quantum Dot Solar Cells and Infrared Photodetectors -- 14. Semiconductor Quantum Dot-Sensitized Solar Cells Employing TiO2 Nanostructured Photoanodes with Different Morphologies -- 15. Optoelectronic Applications of Colloidal Quantum Dots.- Index.
Keywords: Quantum optics; Nanotechnology; Nanoscale science; Nanoscience; Nanostructures; Semiconductors; Lasers; Photonics; Quantum Optics; Nanotechnology; Nanotechnology and Microengineering; Nanoscale Science and Technology; Semiconductors; Optics, Lasers, Photonics, Optical Devices